(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The paper anchored on socio-economic implication of community development and rural transformation in Cross River State. The study was stratified into three senatorial district that made up the State. The communities were purposively selected from Yakurr, Calabar South and Ogoja Local Government Area. Four hundred copies of questionnaire were administered using a descriptive design, simple percentage frequency and interview guide. One hypothesis was tested and formulated using Pearson moment correlation. The finding revealed that, there is a significant relationship between socio-economic implication of community development to the provision of healthcare, roads educational facilities and electricity with rural transformation in Cross River State. It is on this note that the paper recommends, the provision of educational facilities as a way of developing skills and knowledge acquisition that will help to meet up the 21st century challenge in Cross River State.